2011
DOI: 10.7439/ijbr.v2i1.79
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperlipidemic Potential of Fruits of Tribulus Terrestris Linn.

Abstract: The aqueous extract of fruits of Tribulus terrestris was tested for its effect on cholesterol induced hyperlipidaemia in rats. The study with aqueous extract at dose of 580 mg/kg body weight showed significant reduction in various biochemical parameters (LDL, VLDL, TC, TG &AI) and increase in HDL level than aqueous extract at dose of 300 mg/kg body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
(3 reference statements)
0
11
0
Order By: Relevance
“…This result partially matches with the evaluation from Sen et al, (2011); describing that, elevated serum TG level was decreased in extract and Sprulina treated group. Hypolipidemic activity may be due to the presence of phenolic compounds leading to increased lipoprotein lipases in the muscles and decreased activity in the adipose tissues, thus indicating that plasma triglycerides are utilized for energy production by the muscle and not for energy storage by the adipose tissue (Khan et al, 2011). Nugroho et al, (2014) estimated that Spirulina has significant lowering effect on triglyceride levels in high fructose fed diabetic rats in contrast to normal rats.…”
Section: Discussionmentioning
confidence: 99%
“…This result partially matches with the evaluation from Sen et al, (2011); describing that, elevated serum TG level was decreased in extract and Sprulina treated group. Hypolipidemic activity may be due to the presence of phenolic compounds leading to increased lipoprotein lipases in the muscles and decreased activity in the adipose tissues, thus indicating that plasma triglycerides are utilized for energy production by the muscle and not for energy storage by the adipose tissue (Khan et al, 2011). Nugroho et al, (2014) estimated that Spirulina has significant lowering effect on triglyceride levels in high fructose fed diabetic rats in contrast to normal rats.…”
Section: Discussionmentioning
confidence: 99%
“…Hypolipidemic activity may be due to the presence of phenolic compounds leading to increased lipoprotein lipases in the muscles and decreased activity in the adipose tissues, thus indicating that plasma triglycerides are utilized for energy production by the muscle and not for energy storage by the adipose tissue. [ 37 ] The pleotropic effect of TT at 5 mg/kg/day dose for 8 weeks on the lipid profile and vascular endothelium of the abdominal aorta in New Zealand rabbits fed on a cholesterol-rich diet was studied. It was found that dietary intake of the herb significantly lowered the serum lipid profile, decreased endothelial cellular surface damage as well as ruptures, and partially repaired the endothelial dysfunction resulting from hyperlipidemia.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…TT is commonly used as medicinal herb in the treatment of various diseases in many countries. The induction of bone formation due to an increase in testosterone production [12] and hypolipidemic activities [25,44] have been reported as consequences of TT treatment in several studies. However, its effect is not known on BMD in cases caused by hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plants are known to have an important impact on human health throughout in the world [22]. aphrodisiac [24], hypolipidemic [25],…”
Section: Introductionmentioning
confidence: 99%